A quantitative method for the determination of bosutinib in human plasma using high‐performance liquid chromatography and ultraviolet detection. Issue 1 (4th April 2017) - Sumimoto, Takahiro; Nakahara, Ryosuke; Sato, Yuhki; Itoh, Hiroki
Abstract : Background: We propose a simple, sensitive, and fast high‐performance liquid chromatography ultraviolet detection (HPLC‐UV) method for the quantitative determination of bosutinib in human plasma. Methods: Plasma samples were processed using an Oasis hydrophilic‐lipophilic balance extraction cartridge (1 mL, 30 mg). Bosutinib and the internal standard imatinib were separated using a mobile phase of 0.5% Na2 PO4 H2 O (pH 3.5)‐acetonitrile‐methanol (55:25:20, v/v/v) on a CAPCELL PAK C18 MG II reversed‐phase column 250 nm×4.6 nm i.d., at a flow rate of 1.0 mL/min, with ultraviolet detection at 250 nm. Results: The calibration curve exhibited linearity over the bosutinib concentration range of 25‐1500 ng/mL at 250 nm, with coefficient of variation for intraday precision of 2.42%, 6.04%, and 1.11% for 100, 250, and 1500 ng/mL, respectively, of bosutinib. The lower limit of detection was 20 ng/mL. The extraction recovery rates for bosutinib ranged from 84.36% to 85.82%. The intra‐ and interday precision was below 8.7%, and the accuracy ranged from −5.95% to 5.85% over the linear range. No notable matrix effects or astaticism were observed. Conclusion: The proposed HPLC‐UV method was successfully applied as an assay to detect bosutinib in human plasma.